2017
DOI: 10.1002/ece3.3086
|View full text |Cite
|
Sign up to set email alerts
|

Who's My Daddy? Considerations for the influence of sexual selection on multiple paternity in elasmobranch mating systems

Abstract: Polyandry resulting in multiply‐sired litters has been documented in the majority of elasmobranch species examined to date. Although commonly observed, reasons for this mating system remain relatively obscure, especially in batoids. The round stingray (Urobatis halleri) is an abundant, well‐studied elasmobranch distributed throughout the northeastern Pacific that we used to explore hypotheses regarding multiple paternity in elasmobranchs. Twenty mid‐ to late‐term pregnant females were sampled off the coast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…Males' perception of their degree of intraspecific competition is often inferred through reproductive morphometrics in a population, specifically comparing relative testes mass as a proxy for sperm production capability (Kenagy & Trombulak, 1986; Moller & Briskie, 1995; Stockley et al, 1997). In round stingrays, high variation in testes mass suggests that males perceive their degree of intrasexual competition to be high, which is likely considering the high density of stingrays in sampling locations (Lyons et al, 2017). In small‐spotted catsharks, other male reproductive tract morphometrics (epididymis and seminal vesicle diameter, clasper length, testes mass) are significantly larger in one population, which authors attribute to possible differences in sperm competition (Finotto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males' perception of their degree of intraspecific competition is often inferred through reproductive morphometrics in a population, specifically comparing relative testes mass as a proxy for sperm production capability (Kenagy & Trombulak, 1986; Moller & Briskie, 1995; Stockley et al, 1997). In round stingrays, high variation in testes mass suggests that males perceive their degree of intrasexual competition to be high, which is likely considering the high density of stingrays in sampling locations (Lyons et al, 2017). In small‐spotted catsharks, other male reproductive tract morphometrics (epididymis and seminal vesicle diameter, clasper length, testes mass) are significantly larger in one population, which authors attribute to possible differences in sperm competition (Finotto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario sperm from individual males only gain access during specific ovulation windows, leaving subsequent ovulations open to other males. This has been hypothesized to occur in round stingrays where examination of sireship placement of embryos in the right and left uteri indicated that females may cryptically alter ovulation patterns to produce more evenly skewed litters (Lyons et al, 2017). Other species, such as nurse sharks, have protracted ovulation windows where females release eggs over the course of several weeks (Castro, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PCBs are known to have estrogenic as well as antiestrogenic endocrine‐disrupting effects depending on model and factors tested (Hany et al ; Kaya et al ), which could contribute to this negative effect on male embryonic growth. Small size in early life could have lasting negative effects on male fitness as male to male competition is high in mainland round stingrays (Lyons et al ).…”
Section: Discussionmentioning
confidence: 99%
“…b) and hence increased sperm production would be beneficial for fertilization success. Polyandry resulting in multiply‐sired litters is well confirmed for Chondrichthyes (Lyons et al ., ) and therefore effective and efficient sperm production is probably associated with the risk of sperm competition.…”
Section: Discussionmentioning
confidence: 99%